2017
DOI: 10.1002/gps.4816
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of a communication intervention for family caregivers and spouses with dementia

Abstract: At home dyadic, relationship-focused psychoeducational intervention to improve communication in spouses affected by dementia has the potential to improve communication outcomes. Creative ways of working with couples are needed to help them sustain their relationships and maintain their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…There is an increased risk that this will only require more intense coping strategies, pronounced loneliness and health risks. There is a need to support these spouses as individuals with different interventions, such as training that will help them to care for their spouse in tried and tested ways, as the intervention by (Williams & Parker, 2012b;Williams, Newman, et al, 2017a;Williams, Newman et al, 2017b). In any further research, it would be interesting to analyze which subject positions spouses find possible and meaningful after having received that kind of support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increased risk that this will only require more intense coping strategies, pronounced loneliness and health risks. There is a need to support these spouses as individuals with different interventions, such as training that will help them to care for their spouse in tried and tested ways, as the intervention by (Williams & Parker, 2012b;Williams, Newman, et al, 2017a;Williams, Newman et al, 2017b). In any further research, it would be interesting to analyze which subject positions spouses find possible and meaningful after having received that kind of support.…”
Section: Resultsmentioning
confidence: 99%
“…It could thereby be argued that there is a need for extended support in order to maintain the relationship. Williams (2015) suggests that it is important to relate to the other with compassion and to trust in the existence of the attachment of the marriage, and that these aspects should be articulated in the communication (Williams, 2015;Williams, Newman, et al, 2017b;Williams & Parker, 2012b). However, as in any relation, taking care for yourself is important, which can be problematic when living with a spouse with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest, based on our results and in line with Hernandez et al (), that practitioners should help couples to strengthen their bond so as to maintain a sense of well‐being and to carefully assess the well‐being of couples whose relationship is relatively new at the time one partner is diagnosed with dementia. A way of doing this might be to use the CARE intervention on emotional communication as described by Williams et al (). Further, Lasrado et al () suggested a home‐based couple management guide (DemPower) that focused on activities that can be done together as a tool to increasing the sense of togetherness.…”
Section: Discussionmentioning
confidence: 99%
“…Wadham et al () described the importance of decade‐long relationships as being a basis for sustaining couplehood during challenging times. Williams and colleagues (Williams, ; Williams, Newman, & Hammar, ) stated the importance of couples being able to engage in emotional communication in order to sustain their relationship. They developed a home‐based intervention—Caring About Relationships and Emotions (CARE)—to improve communication and to support the relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation